Klinični potek in zdravljenje Fabryjeve bolezni pri treh bolnikih pred uvedbo nadomestnega encimskega zdravljenja - Verovnik, Franc (Zdravniški vestnik, 2006)
Background Fabry disease (FD) is an X-linked inherited disorder of glycosphingolipids metabolism. Clinical manifestations, the course and the cause of death are markedly different among the patients. Before the use of enzyme replacement therapy patients with FD died early in their life. Methods Following the medical recordings, in this paper the clinical courses and causes of death are described for three patients with FD who died before the introduction of the enzyme replctcement therapy. Results Although three patients were brothers and had the same gene mutation, the clinical manifestations of FD were completly different in each of patient. The first had early neurogical symptoms, the second problems with heart and the third had early deterioration of renal function. They died early despite all possible therapeutic measurements. Conclusions Early recognition of FD is extremely important. Nowadays it is possible to prevent the fatal complications and early death by means of modern effective enzyme replacement therapy.
Keywords: dedne bolezni; Diagnosis; Drug Therapy; Fabryjeva bolezen; Fabry's Disease; Middle Age; Srednja leta; therapy; zdravljenje